2021
DOI: 10.1186/s13046-021-02141-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting strategies for oxaliplatin-induced peripheral neuropathy: clinical syndrome, molecular basis, and drug development

Abstract: Oxaliplatin (OHP)-induced peripheral neurotoxicity (OIPN) is a severe clinical problem and potentially permanent side effect of cancer treatment. For the management of OIPN, accurate diagnosis and understanding of significant risk factors including genetic vulnerability are essential to improve knowledge regarding the prevalence and incidence of OIPN as well as enhance strategies for the prevention and treatment of OIPN. The molecular mechanisms underlying OIPN are complex, with multi-targets and various cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 207 publications
(272 reference statements)
0
39
0
Order By: Relevance
“…As a bifunctional alkylating agent, OX could interfere with DNA replication and ultimately induce apoptosis of tumor cells [41][42][43]. Despite oxaliplatin-based chemotherapy being successfully applied for colorectal cancer therapy, OX could lead to serious side effects, such as neurotoxicity due to non-speci c uptake [44][45][46]. Moreover, it is less effective for tumor cells with MDR.…”
Section: Cytotoxicity and Cytophagocytosis Experiments Of Ox@se-mnpmentioning
confidence: 99%
“…As a bifunctional alkylating agent, OX could interfere with DNA replication and ultimately induce apoptosis of tumor cells [41][42][43]. Despite oxaliplatin-based chemotherapy being successfully applied for colorectal cancer therapy, OX could lead to serious side effects, such as neurotoxicity due to non-speci c uptake [44][45][46]. Moreover, it is less effective for tumor cells with MDR.…”
Section: Cytotoxicity and Cytophagocytosis Experiments Of Ox@se-mnpmentioning
confidence: 99%
“…As with CDDP and CP, OXP has limitations to its use, either because of side effects, hypersensitivity, or chemoresistance. The major dose-limiting side effect of OXP is peripheral neurotoxicity, occurring acutely or chronically [252,260,[289][290][291]. Acute OXP-induced peripheral neuropathy (OIPN) occurs in the majority of patients and can be exacerbated by cold stimulation; the symptoms begin to present within hours of the infusion and can last up to 7 days [252,291].…”
Section: Limitations Of the Use Of Oxaliplatinmentioning
confidence: 99%
“…Up until now, several researchers have reported that severe damage in Dorsal Root Ganglion (DRG) neurons leads to the development of PN [ 17 , 18 , 19 , 20 ]. In particular, it was found that oxaliplatin causes the selective atrophy of a subpopulation of dorsal root ganglion neurons, large DRG neurons (≥1000 μm 2 ), without interfering with total DRG neuronal cell number [ 21 ].…”
Section: Introductionmentioning
confidence: 99%